'Russia is interested in the Petsamo nickel' (Juho Kusti Paasikivi in telegram to Finland's MFA, 23 June 1940)1. Issue 1 (2nd January 2020) - Rowe, Lars
ABSTRACT: In June 1940, Vyacheslav Molotov demanded access to the nickel resource in Finnish Petsamo. Just three months earlier, the area had been returned to Finland as part of the Moscow Peace Treaty. What had changed to ignite Molotov's interest? Geopolitical factors have traditionally been accorded weight in explanations of the Soviet turnaround. This article, however, contends that power politics cannot fully account for the sudden Soviet interest, but that industrial aspirations must also be considered. In October 1944, Finnish Petsamo became Soviet Pechenga, and was hastily enrolled in the planned economy. Moscow's sustained interest in the area while it was controlled by Nazi forces, would suggests that industrial ambitions were always at the core of Soviet designs on Petsamo.